Anatomia de Nudibrânquios Facelinídeos (Gastropoda: Opisthobranchia) do Nordeste do Brasil, Atlântico Sul - Moreira, Ana Karla Araújo (2013)
The family Facenilidae is represented in Brazil by nine species, of which three are found in the Northeast region: Phidiana lynceus Bergh, 1897; Phidiana riosi Gracía & Troncoso, 2003; and Nanuca sebastiani Marcus, Er. 1957. This study presents a new species of the genus Cratena, and also records Dondice cf. occidentalis for the first time in Northeast Brazil. The examined material came from the beaches of Pacheco, Iparana, Caponga and Banco dos Cajuais, in the state of Ceara; from Marine Biological Reserve Rocas Atoll, an oceanic island belonging to the estate of Rio Grande do Norte; besides material arising from the collection of the Museum of Zoology, USP. The analyzed species present three patterns regarding the radula morphology. The first pattern is present in Cratena sp., the second in Dondice occidentalis and Nanuca sebastiani and the third in Phidiana lynceus and P. riosi. The analyzed species present the masticatory edge of the jaw with a single row of denticles. The species P. lynceus and P. riosi have, in general, a similar reproductive system as to the shape of the ampulla, which is twisted or curved, also the absence of the bursa copulatrix and the presence of a hook-shaped thorn in the penis. The specimens of Dondice cf. occidentalis analyzed it matched with the description of the genus by Marcus (1958), except for not presenting the prostate as a separate gland. The unarmed penis with a proximal accessory gland are characteristics that refer to the genus Cratena Bergh, 1864. These features corroborate with observation of the specimens, and therefore can be considered as belonging to the genus Cratena. The specimens of Nanuca sebastiani analyzed here showed differences in the reproductive system when compared with the description of the species. More detailed taxonomic studies, complemented with biological data, are necessary for a better knowledge of this group.